Endobronchial metastases secondary to prostate cancer: A case report and literature review. (2021) - Hameed, Mansoor; Haq, Irfan Ul; Yousaf, Muhammad; Hussein, Mousa; Rashid, Umar; Al-Bozom, Issam
Abstract: Metastatic disease from solid extrapulmonary tumours affects the lungs frequently. Endobronchial metastases (EM) however are very rare. Most commonly breast, colorectal and renal carcinomas can result in endobronchial metastases. EM secondary to a prostate primary are even more uncommon. We present an unusual case of a synchronous diagnosis of EM and primary prostate cancer. The diagnosis was confirmed on bronchoscopic endobronchial biopsies and immunohistochemical examination. Just 3 such cases have been reported to the best of our knowledge in the last 15 years. We discuss frequencies, similarities with previously reported cases, possible developmental modes and the diagnosis of EM. We conclude that patients with a current or previous diagnosis of an extrapulmonary malignancy with apparently trivial respiratory symptoms and/or unexplained weight loss should be considered for a bronchoscopy. Bronchoscopy and immunohistochemical profiling is the gold standard for diagnosing EM, as they may not be visible on cross sectional imaging.